MEDIATION IN EDUCATION AND DEVELOPMENT OF CONFLICTOLOGICAL COMPETENCE OF THE TEACHER - Yuferova, Marina; Koryakovtseva, Olga; Bugaichuk, Tatyana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The history of mankind confirms: both harmony and conflict are characteristic of communication in society. This article is devoted to the problem of conflicts in education. Unfortunately, conflict interaction occurs in school life, therefore, teachers need to learn how to apply innovative technologies in resolving conflicts, focus on respecting the rights and freedoms of all participants in the educational process, and act in accordance with the interests of the parties. The article discusses the technology of mediation, which orients the participants in the interaction towards cooperation in the conflict with the help of a mediator. The implementation of mediation practice requires special training of teachers, the formation of completely new competencies and, first of all, conflict management, which should be developed within the framework of continuous pedagogical education, using interactive training technologies and role-playing games. The authors present the experience of implementing the advanced training program “successful strategies of behavior in conflict and the development of a teacher's resistance to conflict”.